A Novel Plant Specimen Detection Technique using IoT - S. Praveen Chakkravarthy, N. Sandhyarani (Mathematical Statistician and Engineering Applications, 2022)
Ayurveda is a traditional Indian medical system that aims to maintain health and wellness by balancing the mind, body, and spirit and preventing disease rather than treating it. According to the World Health Organization, traditional medicine, primarily in the form of plant drugs, is used by the majority of the population in developing countries to meet their healthcare needs. From ancient times to the present, medicinal herbs have played an important role in Ayurvedic treatment. The essence of Ayurveda and Ayurvedic treatments is medicinal plants that are locally available in various parts of our country. Many diseases can be cured by using natural herbs found in various parts of the country. However, the blooming season and location of availability of these herbs are not known. The primary goal is to create a prototype that determines the evolution of various rare available herbs that can be used to treat diseases in our country. A Node is placed on a specific plant in an area where the species is present, and all growth details are sensed. All sensed values are updated in the cloud accordingly, The user can view the data collected regarding the stage of growth and blossoming of the flower at any time and from any location easily and comfortably. The following data are analyzed that includes determining the angle of the leaf, which predicts the growth of a specific species. The results support the species' blossoming period